Y : the last man. Vol. 02 Cycles - Vaughan, Brian K. (Vaughan, Brian K. Y the last man, 2003)
It's 2002, and a plague of unknown origin has killed all of the male mammals on Earth-all except an amateur escape artist named Yorick Brown and his surly helper monkey, Ampersand. As the last remaining & -chromosome carriers on the planet, Yorick and his pet hold the fate of humanity in their hands. To ensure the survival of the species, they've teamed up with a gun-toting government agent and the world's premier bioengineer to discover the secret behind the plague. But while they ride the rails across a radically transformed America, the man-hating Daughters of the Amazon are right behind them-and an unplanned stopover in the seemingly utopian town of Marrisville, Ohio may mean the end of the line for the Last Man.